PERANCANGAN SISTEM INFORMASI PENJUALAN PRODUK SEPATU UMKM BERBASIS WEBSITE - Achmad Ainun Zachy; Izzatul Umami; Muhammad Gugus Azhari (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
Internet technology is an effective and efficient information medium in disseminating information. which can be accessed by anyone and anywhere. The use of internet media in this increasingly modern era is utilized as a means of information and communication globally with the aim of increasing business so that it can reach consumers in various regions. SMEs and other micro-entrepreneurs are now using the internet as a way to market the products they sell, which is rather easy to find and reach a wider range of consumers. have to come to the store to buy the item. This research is designed so that MSME business actors of shoe craftsmen can become an online shop that sells goods that have been produced in order to reach a wider market with a variety of shoe products that vary in order to attract buyers. The function of this online store is also so that consumers can obtain information about various kinds of shoes that will be sold easily and efficiently, in various kinds of shoes that are displayed in the form of product images as well as information related to products and product prices being marketed. For this reason, in order to increase sales, this idea is taken into consideration and there is a need for follow-up to build a website-based application in the form of an online shop to help MSME business actors in marketing various products.